Yurchenko I.V. Existence of l-moment of the Strong Solution of Stochastic Integral Differential Ito-Volterra Equation // The International Scientific Periodical Journal "SWorldJournal".– 2021.– Issue №8, Part 2.– Published by: SWorld & D.A. Tsenov, Academy of Economics, Svishtov, Bulgaria.– P.27-34. - Yurchenko, Igor Valeryjovych (Published by: SWorld & D.A. Tsenov, Academy of Economics, Svishtov, Bulgaria., 2021)
In this article the existence of l-moment of the strong solution of stochastic integral differential Ito-Volterra equation is proved in the case of Wiener disturbances and Poisson switchings.
None
Keywords: stochastic integro-differential equation, Wiener disturbances, Poisson switchings, existence of the solution.